Doubling the known diversity of a remote island fauna: marine bivalves of the Juan Fernández and Desventuradas oceanic archipelagos (Southeastern Pacific Ocean) - Zelaya,Diego Gabriel; Güller,Marina; Bieler,Rüdiger (PeerJ, 2024)
Juan Fernández and Desventuradas are two oceanic archipelagos located in the southeastern Pacific Ocean far off the Chilean coast that received protected status as marine parks in 2016. Remoteness and access difficulty contributed to historically poor biodiversity sampling and limited associated research. This is particularly noticeable for bivalves, with most prior regional publications focused on single taxa or un-illustrated checklists. This study investigates marine bivalves collected between the intertidal and 415 m depth during (1) the 1997 IOC97 expedition aboard the M/V Carlos Porter, with special focus on scuba-collected micro-mollusks of both archipelagos, (2) two expeditions by the R/V Anton Bruun (Cruise 12/1965 and Cruise 17/1966), and (3) Cruise 21 of USNS Eltanin under the United States Antarctic Program, which sampled at Juan Fernández in 1965. Also, relevant historical material of the British H.M.S. Challenger Expedition (1873–1876), the Swedish Pacific Expedition (1916–1917), and by German zoologist Ludwig H. Plate (1893–1895) is critically revised. A total of 48 species are recognized and illustrated, including 19 new species (described herein) and six other potentially new species. The presence of two species mentioned in the literature for the region (Aulacomya atra and Saccella cuneata) could not be confirmed. The genera Verticipronus and Halonympha are reported for the first time from the Eastern Pacific, as are Anadara and Condylocardia from Chilean waters. Lectotypes are designated for Arca (Barbatia) platei and Mytilus algosus. These findings double the number of extant bivalve species known from the Juan Fernández and Desventuradas archipelagos, highlighting the lack of attention these islands groups have received in the past. A high percentage of species endemic to one or both archipelagos are recognized herein, accounting for almost 78% of the total. The newly recognized level of bivalve endemism supports the consideration of Juan Fernández and Desventuradas as two different biogeographic units (Provinces or Ecoregions) of the Eastern Pacific Ocean.
Keywords: Biodiversity; Endemism; Expeditions; Marine protected areas; Mollusca; Collections; Oceanic islands; Chile; Bivalvia